Barley flour (áleuron kríthinon) in ancient and early Byzantine medicine (I – VII c. AD) - Jagusiak, Krzysztof; Kokoszko, Maciej (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
The following article attempts to address two issues. The first one concerns dietetic characteristic of barley flour, which was a very popular product used both in Graeco-Roman and Byzantine culinary art and medicine. The second one deals with the therapeutic role of this product: different forms of remedies made from it, its effects on the human body, and various health problems cured by an application of medicines containing aleuron krithinon. To address these questions we study ancient and Byzantine Greek medical sources written between the 1st and 7th century AD by Dioscurides, Galen, Oribasius, Aetius of Amida, Alexander of Tralles, Paul of Aegina, and the anonymous author of the treatise entitled De cibis.